2022
DOI: 10.3389/fpls.2022.799201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutrient (NPK) Factors on Growth, and Pharmacodynamic Component Biosynthesis of Atractylodes chinensis: An Insight on Acetyl-CoA Carboxylase (ACC), 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMGR), and Farnesyl Pyrophosphate Synthase (FPPS) Signaling Responses

Abstract: In the planting of crops, especially medicinal plants, formula fertilization is important for improving the utilization rate of elements, soil quality, crop yield, and quality. Therefore, it is important to study targeted fertilizer application schemes for sustainable agricultural development and environmental protection. In this study, an L9(34) orthogonal design was used to conduct a field experiment to study the effects of NPK combined application on the growth and pharmacodynamic component biosynthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In this study, precise NPK application rates and proportions were key in increasing ginseng growth and development. First, the growth of ginseng aboveground parts (i.e., plant height and stem and leaf fresh weight) showed high adaptability and responsiveness to the N 1 P 3 K 3 (T3) treatment, which is consistent with applications of P and K fertilizers as keys to the vigorous growth of leaves on plant stems (Sun et al, 2022 ). Second, ginseng belowground biomass (i.e., rhizome fresh and dry weights) was also analyzed because rhizome biomass directly determines yields of medicinal materials.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In this study, precise NPK application rates and proportions were key in increasing ginseng growth and development. First, the growth of ginseng aboveground parts (i.e., plant height and stem and leaf fresh weight) showed high adaptability and responsiveness to the N 1 P 3 K 3 (T3) treatment, which is consistent with applications of P and K fertilizers as keys to the vigorous growth of leaves on plant stems (Sun et al, 2022 ). Second, ginseng belowground biomass (i.e., rhizome fresh and dry weights) was also analyzed because rhizome biomass directly determines yields of medicinal materials.…”
Section: Discussionmentioning
confidence: 67%
“…Growth characteristics reflect the adaptability of plants to the soil environment and are important indexes to evaluate plant vitality (Sun et al, 2022 ). Compared with CK, plant height increased in the fertilization treatments, except in T9, and the increases of 1.24-fold in T3 and 1.22-fold in T7 were significant ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, biological entities react to extraneous and internal factors in a DDG patterns which are characterized by three growth phases; stimulation, neutral and inhibition in support of the theory suggested by Liu et al [10] In the present study, at lower rates of NPK fertilizer high level of growth was achieved. Similarly, growth of Actinidia chinensis, plant height and stem leaf fresh weight showed better adaptability and responsiveness to the lower fertilizer dose [11]. Correspondingly, Du et al reported that after 20 days of planting tomato, fresh and dry weight of tomato leaves increased with a decreasing fertilizer rates [12].…”
Section: Discussionmentioning
confidence: 90%